2020
DOI: 10.1017/jfm.2020.898
|View full text |Cite
|
Sign up to set email alerts
|

On the linear receptivity of trailing vortices

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 58 publications
(188 reference statements)
1
24
1
Order By: Relevance
“…According to Heaton (2007), for non-zero viscosity, σ 0 c is replaced by a large number of closely packed discrete eigenmodes, but a detailed explanation was not given. Numerical observations by Bölle et al (2021) identified randomly scattered eigenvalues in the shaded region in figure 4(b), suggesting that they are the viscous remnants of σ 0 c . Mao & Sherwin (2011), who earlier discovered this region, named it the potential spectrum, denoted σ ν p , and suggested that it could be continuous based on the shape of the surrounding pseudospectra.…”
Section: Spectrummentioning
confidence: 95%
See 4 more Smart Citations
“…According to Heaton (2007), for non-zero viscosity, σ 0 c is replaced by a large number of closely packed discrete eigenmodes, but a detailed explanation was not given. Numerical observations by Bölle et al (2021) identified randomly scattered eigenvalues in the shaded region in figure 4(b), suggesting that they are the viscous remnants of σ 0 c . Mao & Sherwin (2011), who earlier discovered this region, named it the potential spectrum, denoted σ ν p , and suggested that it could be continuous based on the shape of the surrounding pseudospectra.…”
Section: Spectrummentioning
confidence: 95%
“…Since our numerical method was specifically designed not to deal with such non-physical eigenmodes, we do not discuss them further in this paper and clarify that our method is not the tool for those who wish to investigate σ ν f . We remark that Bölle et al (2021) argued that the viscous free-stream spectrum is rather an 'artefact' of the mathematical model of an unbounded domain. With the exception of the viscous free-stream eigenmodes, our numerical method is capable of computing the families of eigenvalues and eigenmodes indicated in figure 4.…”
Section: Spectrummentioning
confidence: 96%
See 3 more Smart Citations